Evaluation of eight satellite and reanalysis precipitation products over Angola: The value of targeted regional assessment for water management - Almeida, Manuel; Zhu, Senlin; Coelho, Pedro (Journal of hydrology. Regional studies, 2025)
The study was conducted in Angola, located in southwestern Africa. Angola faces challenges due to scarce in situ hydro-meteorological data and highly variable climate. Consequently, most hydrological studies have focused on smaller watersheds with better data coverage. This study systematically evaluates eight satellite and reanalysis daily rainfall datasets (ARC v2.0, MSWEP v2.8, RFE v2.0, CHIRPS v2.0, TAMSAT v3.1, ERA5L, PERSIANN-CDR, IMERG v06B) across Angola from 2011 to 2023. The assessment covers multiple temporal scales—including full year, wet and dry seasons, extreme quantiles (5th and 95th percentiles), and annual totals—using five continuous and four categorical performance metrics. Results show that daily precipitation is generally poorly captured by all datasets, with no single product consistently excelling across all scales. However, MSWEP v2.8 and IMERG v06B outperform the others. All datasets detect dry conditions (precipitation below 1 mm) reliably but struggle with higher rainfall intensities. MSWEP v2.8 and IMERG v06B show reasonable skill (KGE values up to 0.4) in specific regions, especially the arid southwest provinces of Namibe and Huíla. This highlights the value of targeted regional evaluations for effective water management. The study stresses the need for site-specific assessments before using these datasets in hydrological modeling and recommends prioritizing MSWEP v2.8, IMERG v06B, CHIRPS v2.0, and PERSIANN-CDR for such evaluations. [Display omitted] •All satellite and reanalysis datasets poorly characterize daily rain in Angola.•No single product performs well across all temporal and spatial scales.•MSWEP v2.8 and IMERG v06B outperform others across most timescales.•All datasets skillfully detect no precipitation (<1 mm).•Targeted regional evaluations improve water management efficiency.